2006
DOI: 10.1086/508864
|View full text |Cite
|
Sign up to set email alerts
|

Outflows of Very Ionized Gas in the Centers of Seyfert Galaxies: Kinematics and Physical Conditions

Abstract: All together indicate a stratification in the ionized gas, usually interpreted in terms of nuclear photoionization as the driving ionization mechanism. However, CL profiles show various peculiarities: they are broader by a factor of 2 than lower ionization lines, the broadening being in terms of asymmetric blue wings, and their centroid position at the nucleus is blueshifted by a few hundred km s À1 . Moreover, in NGC 1386 and NGC 1068, a doublepeaked [Fe vii] line is detected in the nuclear and extended coron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
132
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(158 citation statements)
references
References 33 publications
24
132
1
1
Order By: Relevance
“…Given previous reports of spectroscopic binary AGN candidates (with double-peaked [O iii], and perhaps Hβ), SDSS J1316+1753 suggests itself as another candidate which, in particular, has all of its emission lines double-peaked. However, line splitting of individual or all emission lines has also occasionally been observed before in single AGNs (e.g., Heckman et al 1981;Veilleux 1991aVeilleux , 1991bRodriguez-Ardila et al 2006), and in a few compact radio sources (e.g., Holt et al 2008). It has been suggested to be linked to the geometry of, or local physics in, the NLR, or the influence of radio jets.…”
Section: Discussionmentioning
confidence: 72%
“…Given previous reports of spectroscopic binary AGN candidates (with double-peaked [O iii], and perhaps Hβ), SDSS J1316+1753 suggests itself as another candidate which, in particular, has all of its emission lines double-peaked. However, line splitting of individual or all emission lines has also occasionally been observed before in single AGNs (e.g., Heckman et al 1981;Veilleux 1991aVeilleux , 1991bRodriguez-Ardila et al 2006), and in a few compact radio sources (e.g., Holt et al 2008). It has been suggested to be linked to the geometry of, or local physics in, the NLR, or the influence of radio jets.…”
Section: Discussionmentioning
confidence: 72%
“…Shock velocities greater than 200 km s −1 produce strong free-free X-ray emission and thus can be the cause of the observed extended X-rays and, in turn, additionally contribute to the H2 excitation. (Rossa et al 2000;Bennert et al 2006;Rodríguez-Ardila et al 2006). Moreover, evidence of an extended coronal emission was reported by Rossa et al (2000) and Rodríguez-Ardila et al (2006), who found that [Fe vii] λ6087Å is emitted in a region of ∼ 100 pc in radius from the the centre.…”
Section: Excitation Of the Molecular Gasmentioning
confidence: 83%
“…The use of the high ionization coronal line emitting spectrum as a signature of energetic AGN-driven outflows at scales of few pc from the centre allowed Rodríguez-Ardila et al (2006) to open a new window to explore this subject. Because of their high-ionization potential ( 100 eV), these lines are genuine tracers of the presence of an AGN (Penston 1984;Marconi et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The [SiVI] line has a high ionisation potential (167 eV) and it is associated with Seyfert activity where the gas is ionised outside the broad line region of the AGN (Bedregal et al 2009). The [SiVI] emission is usually rather compact, concentrated around the unresolved nucleus and extending up to a few tens or a few hundred parsecs in some Seyferts (Prieto et al 2005;Rodríguez-Ardila et al 2006). While in galaxies like IRASF 12115-4656 and IRAS 23128-5919 the emission is unresolved (i.e.…”
Section: Coronal Line Emissionmentioning
confidence: 99%